Sistem Pendukung Keputusan Dalam Menentukan Jenis Pohon Pelindung Yang Akan di Tanam Dipinggir Jalan Menggunakan Metode Promethee II - Ardian Fadly Telaumbanua; Muhammad Syahrizal; Murdani Murdani (Jurnal Sistem Komputer dan Informatika (JSON), 2020)
A protective tree is a group of plants that have long canopy and thick leaves and trunk high enough to be a shade. Usually a protective tree becomes the main plant in a park. But what we often see is the protective tree planted along the road. Its function aside from being a shade tree is also intended to absorb pollution. It is necessary to determine the selection of the best tree species to be planted on the side of the road. The selection of protective tree species still uses a manual system and requires quite a long time. Based on these problems, we need a decision support system (SPK) that can facilitate the selection of the best protective tree species using existing criteria. One method that can be used is the Preference Ranking Organization Method for Enrichment Evaluation II (PROMETHEE II). This method is able to solve any type of problem in decision making with alternatives and criteria that have been given weight. Research using PROMETHEE II produces the composition of the usual protective trees to the best protective trees. The protective tree selection system was built using Microsoft Visual Studio 2008 and Microsoft Access 2010 as a database.